CCR4 is an up-regulated chemokine receptor of peripheral blood memory CD4(+) T cells in Crohn's disease - JO, Y (Blackwell Science Inc, 2003)
Several chemokine receptors are expressed selectively on the surface of T cells depending on their polarization. The aim of this study was to characterize chemokine receptor expression in peripheral blood memory T cells in Crohn's disease (CD) and ulcerative colitis (UC), and to correlate the expression with disease activity. Peripheral blood mononuclear cells (PBMCs) were obtained from 24 patients with CD, 30 patients with UC, 24 normal controls and 10 disease controls. PBMCs were stained by anti-CCR3, CCR4, CCR5, CXCR3, CD4, CD8, CD45RO and β 7 integrin, and the expression of the chemokine receptors were determined by flow cytometry. CCR4 expression on memory T cells was significantly lower in UC than in CD or normal controls, and that of memory CD4(+) T and β 7(high) memory CD4(+) T cells was significantly higher in CD than in UC or normal controls. CCR4 expression on memory CD4(+) T cells exhibited significant positive correlation with disease activity in CD, and this decreased significantly after treatment. Such a decrease was not found in the disease controls. CCR5 and CXCR3 expression on memory CD8(+) T cells was significantly lower in CD than in normal controls. CXCR3 expression on β 7(high) memory CD4(+) T and CXCR3 expression on memory CD8(+) T cells were lower in UC than in normal controls. These findings suggest that in peripheral blood memory T cells, chemokine receptor expression is different between CD and UC. Enhancement of CCR4 and suppression of CCR5 and CXCR3 seem to be the characteristic chemokine receptor profile in peripheral blood memory T cells of CD.